2021
DOI: 10.1111/jems.12431
|View full text |Cite
|
Sign up to set email alerts
|

Social efficiency of entry: Implications of network externalities

Abstract: We examine the welfare effects of entry in the presence of network externalities. We show that if network goods are fully incompatible, entry is socially insufficient as long as the entry cost is high, the goods are sufficiently differentiated, and the degree of network externality is low. Further, we show that as the degree of compatibility between the network goods increases, insufficient entry becomes more likely. Our findings provide policy guidelines for anticompetitive and procompetitive entry regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…2 Pal and Scrimitore [18] demonstrated that the relationship between collusion sustainability and market concentration in a homogenous oligopoly with network externalities depended on the strength of network externalities. 3 Basak and Petrakis [20] recently showed from the viewpoint of social desirability that as long as the cost of entry is high, entry is socially insufficient if network goods are completely incompatible, the goods are sufficiently differentiated, and the level of network externalities is low. 4 The same utility function is also used by many works; for example, see Naskar and Pal [24], Pal [25,26], Toshimitsu [27,28], and Choi and Lee [19].…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Pal and Scrimitore [18] demonstrated that the relationship between collusion sustainability and market concentration in a homogenous oligopoly with network externalities depended on the strength of network externalities. 3 Basak and Petrakis [20] recently showed from the viewpoint of social desirability that as long as the cost of entry is high, entry is socially insufficient if network goods are completely incompatible, the goods are sufficiently differentiated, and the level of network externalities is low. 4 The same utility function is also used by many works; for example, see Naskar and Pal [24], Pal [25,26], Toshimitsu [27,28], and Choi and Lee [19].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…4 The same utility function is also used by many works; for example, see Naskar and Pal [24], Pal [25,26], Toshimitsu [27,28], and Choi and Lee [19]. 5 Basak and Petrakis [20] provided a simpler expression for the inverse demand function.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The progress in information and communication technology has witnessed a proliferation of products that exhibit network externalities, because of the network goods industries (see Shy, 2001 andBirke, 2009). Recently, Basak and Petrakis (2021) and Toshimitsu (2020) examined the welfare effects of entry in the presence of network externalities. Examples of network goods are smartphones, application software, operating systems and internet service including computers and technology good.…”
Section: Introductionmentioning
confidence: 99%
“…This type of preference function has been widely used in several studies, such as,Hoernig (2012),Chirco and Scrimitore (2013),Pal (2014Pal ( , 2015,Song and Wang (2017),Naskar and Pal (2020),Basak and Petrakis (2021).…”
mentioning
confidence: 99%